Salicornia ramosissima an edible halophyte with nutritional value and a source of a unique natural compound - Isca, Vera M. S. (2015)
PURPOSE: Salicornia ramosissima J. Woods aerial parts are considered, in the Iberian Peninsula and France, a gourmet product mainly because of its salty taste. Nevertheless, its metabolomic profile is still unknown. As a part of our continuing search for structurally interesting natural products from plants, the aerial parts of S. ramosissima were phytochemically investigated.